2010
DOI: 10.3109/02713680903484259
|View full text |Cite
|
Sign up to set email alerts
|

Differential Vitreous Dye Diffusion Following Microplasmin or Plasmin Pre-Treatment

Abstract: Microplasmin and plasmin have a similar enzymatic effect on vitreous. However, an equipotent amount of microplasmin appears to have a more extended effect on vitreous gel. This may, in part, be related to its smaller size allowing it to diffuse more readily through the vitreous matrix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…In an elegant study, Goldenberg et al 15 demonstrated that bevacizumab was absorbed more quickly through the retina following microplasmin-induced posterior vitreous detachment compared with nontreated eyes in a rabbit model. Gad Elkareem et al 16 demonstrated higher differential fluorescein diffusion rates in both plasmin and microplasmin compared with saline-treated vitreous cavities.…”
Section: Discussionmentioning
confidence: 99%
“…In an elegant study, Goldenberg et al 15 demonstrated that bevacizumab was absorbed more quickly through the retina following microplasmin-induced posterior vitreous detachment compared with nontreated eyes in a rabbit model. Gad Elkareem et al 16 demonstrated higher differential fluorescein diffusion rates in both plasmin and microplasmin compared with saline-treated vitreous cavities.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] Assessment of dispersion was done by ophthalmoscopy or by dissecting the vitreous carefully out of the eye. In this study, a new method was established using an UHRCT scanner and a radio-opaque contrast agent to visualize the dispersion in a 3D-reconstructed manner without any vitreous manipulation.…”
Section: Discussionmentioning
confidence: 99%
“…This has previously been studied either by using Indian ink or fluorescein. [15][16][17] Both colorants are easily visualized in the vitreous cavity, but it is difficult to assess or measure the real size, shape, and dispersion rate of the contrast bubble by ophthalmoscopy. Furthermore, follow-up over a period of hours or days requires in vivo tests because the cornea and lens will hinder visualization in enucleated eyes.…”
mentioning
confidence: 99%
“…9 Ocriplasmin's activity is pH dependent; at a neutral pH, it has a high lytic activity. It hydrolyzes collagen, laminin, and fibronectin.…”
Section: ' Preclinical Studies Of Ocriplasminmentioning
confidence: 99%